Developing critical thinking skills through content-based instruction - Casipit, Arlene Bautista (2008)
This study aimed to determine whether Content-Based Instruction develops critical thinking skills among first year Low English Proficiency students in a public national high school located in San Carlos City, Pangasinan. The subjects underwent a validated researcher-made Critical Thinking Skills Prestest and were then exposed to Content-Based Instruction in which science texts, and other expository texts were utilized. Eight integrated weekly lesson plans were used with emphasis on the development of thinking skills. After 40 sessions, a posttest was administered. Results were analyzed statistically using the overall mean score and frequency counts and percentages. It was concluded that Content-Based Instruction significantly improved the critical thinking skills of the students as well as other reading skills like developing vocabulary, identifying referents, and noting details.
Vita.
Thesis (M.A. Language Education)--University of the Philippines, Diliman.
Keywords: Critical thinking -- Philippines -- San Carlos City (Pangasinan); Content area reading -- Philippines -- San Carlos City (Pangasinan); English language -- Ability testing -- Philippines -- San Carlos City (Pangasinan); Language arts (Secondary) -- Correlation with content subjects -- Philippines -- San Carlos City (Pangasinan); High school students -- Philippines -- San Carlos City (Pangasinan)